Qualitative communication research methods - Lindlof, Thomas R.; Taylor, Bryan C. (SAGE, 2019)
Qualitative Communication Research Methods, Fourth Edition introduces readers to qualitative research in speech and mass communication, providing numerous examples of work in the field to illustrate.